Courses
Courses for Kids
Free study material
Offline Centres
More
Store Icon
Store
Last updated date: 13th Jun 2024
Total views: 384k
Views today: 5.84k
Answer
VerifiedVerified
384k+ views
Hint:
 We first try to explain the concept of factorisation and the ways a factorisation of a polynomial can be done. We use the identity theorem of $ {{a}^{2}}-{{b}^{2}}=\left( a+b \right)\left( a-b \right) $ to factor the given polynomial $ 9{{x}^{2}}-25 $ . We assume the values of $ a=3x;b=5 $ . The final multiplied linear polynomials are the solution of the problem.

Complete step by step answer:
The main condition of factorization is to break the given number or function or polynomial into multiple of basic primary numbers or polynomials.
For the process of factorisation, we use the concept of common elements or identities to convert into multiplication form.
For the factorisation of the given quadratic polynomial $ 9{{x}^{2}}-25 $ , we apply the factorisation identity of difference of two squares as $ {{a}^{2}}-{{b}^{2}}=\left( a+b \right)\left( a-b \right) $ .
We get $ 9{{x}^{2}}-25={{\left( 3x \right)}^{2}}-{{5}^{2}} $ . We put the value of $ a=3x;b=5 $ .
Factorisation of the polynomial gives us
$ 9{{x}^{2}}-25={{\left( 3x \right)}^{2}}-{{5}^{2}}=\left( 3x+5 \right)\left( 3x-5 \right) $ .
These two multiplied linear polynomials can’t be broken anymore.
Therefore, the final factorisation of $ 9{{x}^{2}}-25 $ is $ \left( 3x+5 \right)\left( 3x-5 \right) $ .

Note:
 The formula of $ {{a}^{2}}-{{b}^{2}}=\left( a+b \right)\left( a-b \right) $ derives from the solution identity of
\[\begin{align}
  & {{a}^{2}}-{{b}^{2}} \\
 & ={{a}^{2}}-ab+ab-{{b}^{2}} \\
 & =a\left( a-b \right)+b\left( a-b \right) \\
 & =\left( a+b \right)\left( a-b \right) \\
\end{align}\]